ASSESSMENT OF BIOLOGICAL AGE AND SENSITIVE PERIODS AS ONE INFLUENCE IN THE FITNESS OF SOCCER ATHLETES IN JUVENILE AND CHILDREN (Fiep Bulletin - online, 2011)
This article aims to ascertain the biological age of soccer athletes in child and  juvenile categories, using  Dorokhov's  protocol (1970), and to relate it to the sensitive periods for training capacities, using Filin's and Volkv's  table (1998). The sample was characterized by 33 make soccer athletes, tied to Toledo Colônia Work from Toledo city, state of Paraná, in Brazil; being 15 athletes of the child category (14 and 15 years old), and 18 athletes of the juvenile category (16 and 17 years old). In child and juvenile categories, was observed respectively, the average biological age of 14 (±0,51) and 14,6 (±0,69) and the average chronological age was 14,7 (±0,45) and 16,2 (±0,74), this the capacities with priority for training, according to the schedule of sensitive periods in the both categories would be: strength, coordination, speed/force and flexibility. Then, we can detect that despite the two categories have distinct average biological age, the assessment of the average biological age presented a minimum different average (0.6) between them. From the obtained data this study points out the need to determine the biological age in the child and youth categories of soccer for being considered in planning and implementing the training of motor capacities, prioritizing those that are on their sensitive period.
Keywords: soccer; biological age; sensitive periods; motor capacity